Quick Assessment on the Integrated Livestock Farming System in the Agro-ecological Zone of Manokoari West Papua - D. A. Iyai; A. Yaku (Jurnal Ilmu dan Teknologi Peternakan, 2016)
A modern livestock development needs clarity and state construction, boundary, types and its dynamic production. An explorative study with survey method through Participative Rural Appraisal for one month has been used to gain recordings on resources owned by the farmers in the agroecological zone of Manokwari, including North Manokowari, South  Manokwari, Warmare, Prafi, Masni, Oransbari, Ransiki, Anggi dan Minyambouw. Agroecological characteristics were tabulated using Microsoft Office Visio. Using simple matrix, grouping was carried out according to the criteria, i.e. livestock commodity, crops commodity, fishery commodity, and biophysical components. The findings of this study were that integrated livestock farming systems in the agroecological coastal area was cattle palm farming system (cocobeef) and crops livestock farming system. In addition, backyard poultry farming system was also identified. The farming systems developed in the low-land area were cattle palm farming system, pig palm farming system, goat farming system, poultry farming system and crops livestock farming system. In highland agroecological zone, crop pig farming system, poultry farming system dan backyard cattle farming system have been developed.